2017-2019 Sudden cardiac death registry of the Zabaykalsky Krai population (ZODIAC) - D. N. Zaitsev; P. V. Vasilenko; A. V. Govorin; E. A. Vasilenko; N. V. Mukha; A. P. Filev; A. N. Brizhko; N. G. Petrova; E. A. Sazonova (Российский кардиологический журнал, 2020)
Aim. Based on the autopsy data, to analyze mortality patterns of the Zabaykalsky Krai population over a three-year period in the group of out-of-hospital sudden cardiac death (SCD).Material and methods. The protocols of deceased persons without evidence for violent death were analyzed with distribution into groups depending on age, sex and cause of death. Descriptive statistics were used for statistical processing.Results. The leading positions (58% of cases) in mortality patterns are occupied by various types of coronary artery disease (CAD). Chronic coronary syndromes were detected in 21%, cardiomyopathy — in 11%, decompensated heart failure — in 7%, myocarditis — in 1% of cases. Acute types of CAD were found in 68,4% in men and 31,6% in women. Among men, the number of such cases increases from 31 to 70 years of age and decreases over 70 years old. Among women, there is an increase in the SCD prevalence in the group over 70 years old.Chronic coronary syndromes were found in 46,4% in men and 53,6% in women. In both groups the number of cases increases with age. The maximum sex differences are observed in the group over 70 years old. The mean age for men is 72,2±8,8 years, for women — 77,2±10,4 years. Blood alcohol was detected in 10,2% of cases. The mean age of the deceased in all age groups of persons with identified blood alcohol was 66,2±12 years.In 1,89% of cases, I46 code (ICD-10) was established. The largest number of deaths among persons of both sexes was registered in the group of 31-40 years old, accounting for 36,8% among men and 13,2% among women. The mean age of the deceased was 35,8±8,4 years. In 28,6% of cases, ethyl alcohol was found in the biological media of the deceased in this group.Conclusion. Acute and chronic types of CAD make a significant contribution to out-of-hospital mortality. The number of SCD in men is higher than in women and is directly proportional to the age increase, reaching a maximum in the group over 70 years old. Ethyl alcohol, an important trigger of SCD, was detected in 10,8% of SCD cases in 2017, and in 15% in 2018 and 2019.